PERLINDUNGAN HUKUM BAGI PASIEN DAN TENAGA MEDIS DALAM INOVASI KESEHATAN DIGITAL: TINJAUAN LITERATUR TERHADAP PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Gunawan Widjaja; Wagiman; Dyah Ersita Yustanti; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (CV. Adiba Aisha Amira, 2025)
Digital transformation in Indonesia's health sector has driven the adoption of innovations such as telemedicine, electronic medical records, and online health applications. These innovations improve service efficiency and access, but also raise challenges related to legal protection for patients and medical personnel. This study aims to analyse the forms of legal protection regulated in various laws and regulations in Indonesia, including the Health Law, the Personal Data Protection Law, and technical regulations from the Ministry of Health. The method used is a literature review with a normative legal approach to regulations and previous research findings. The findings indicate that although various legal instruments have been issued, there are still fragmentation and gaps in the regulations, particularly regarding the protection of patients' personal data and the legal certainty of healthcare professionals' liability in digital healthcare services. Implementation challenges include infrastructure limitations, low digital literacy, and the suboptimal mechanisms for complaints and dispute resolution. Recommendations are aimed at harmonising regulations, strengthening digital literacy, and improving the effectiveness of oversight to create a safe and equitable digital health ecosystem.